The role of fluid reasoning in word recognition. (2nd January 2020) - Guerin, Julia M.; Sylvia, Allison M.; Yolton, Kimberly; Mano, Quintino R.
Abstract : Background: Multiple perspectives on cognitive development, including Cattell's Investment Theory (1963, 1987), suggest that fluid reasoning (G f ) is foundational to the development of academic knowledge and skills. Yet little is known of the role that G f may play in reading achievement, particularly in comparison with a larger literature demonstrating an influential role of crystallised intelligence (G c ) in word recognition. Given the novelty of word recognition for early readers, it is likely that G f plays an influential role in literacy acquisition. Method: Using regression‐based mediation analysis, the present study examined performance of preschool children ( n  = 154) and college‐aged adults ( n  = 114) on measures of G f, G c, phonemic decoding and word recognition. Results: Results show that G f has a significant direct effect on word recognition among preschoolers but not among adults. Moreover, among preschoolers, G f exerted an effect indirectly on word recognition through phonemic decoding (i.e., G f → phonemic decoding →word recognition), as well as through a serial and joint mechanism of G c and phonemic decoding (i.e., G f →G c →phonemic decoding →word recognition). However, among adults, G f exerted an effect onto word recognition only through this joint and serial mechanism and not singularly through phonemic decoding. Conclusions: Present findings link theories of cognitive development with models of reading development, suggesting that while G f may both directly and indirectly invest in word recognition during early literacy acquisition, this investment may shift in adulthood such that G f exerts only indirect effects through crystallised knowledge and skills (i.e., G c and phonemic decoding).